Corrosion of Q235 Carbon Steel in Seawater Containing Mariprofundus ferrooxydans and Thalassospira sp. - Chen, Shiqiang; Deng, Hao; Liu, Guangzhou; Zhang, Dun (Frontiers in Microbiology, 2019)
Iron-oxidizing bacteria (IOB) and iron-reducing bacteria (IRB) can easily adhere onto carbon steel surface to form biofilm and affect corrosion processes. However, the mechanism of mixed consortium induced carbon steel corrosion is relatively underexplored. In this paper, the adsorptions of IOB (Mariprofundus ferrooxydans, M. f.), IRB (Thalassospira sp., T. sp.) and mixed consortium (M. f. and T. sp.) on surface of Q235 carbon steel and their effects on corrosion in seawater were investigated through surface analysis techniques and electrochemical methods. Results showed that local adhesion is a typical characteristic for biofilm on surface of Q235 carbon steel in M. f. and mixed consortium media, which induces localized corrosion of Q235 carbon steel. Corrosion rates of Q235 carbon steel in different culture media decrease in the order: rM. f. > rmixed consortium > rT. sp. > rsterile. The evolution of corrosion rate along with time decreases in M. f. medium, and increases then keeps table in both T. sp. and mixed consortium media. Corrosion mechanism of Q235 carbon steel in mixed consortium medium is discussed through analysis of surface morphology and composition, environmental parameter, and electrochemical behavior.